Composição corporal e exigências nutricionais de energia de cordeiras Santa Inês durante o crescimento obtido pelas técnicas do abate comparativo e respirometria: uso das técnicas do abate comparativo e respirometria - Vandenberg Lira Silva (2014)
This aimed to evaluate the chemical composition of the body and the net energy requirements for maintenance and weight gain of Santa Inês lambs in growing slaughtered in different weights and feeding planes distinct. The experiment was conducted in the Laboratory of Calorimetry and Metabolism of the Federal University of Minas Gerais in the period of november 2010 the april of 2011. Were used fifty seven Santa Ines lambs with 3 the 4 months of age and live weight of 14 a 26 kg making a completely randomized design in a factorial 3 x 2 three slaughter weights (20 kg, 30 kg and 40 kg) and two nutritional planes (ad libitum and restricted). After slaughter, the animal's body was divided into eight components: Carcass, head and feet, skin, gastrointestinal tract, viscera, fat, uterus and mammary gland. The weight of each component was obtained in grams e in relation to empty body weight (% of EBW). The chemical composition were analyzed in terms of fat, protein, minerals and water, in grams and in g/kg EBW and energy in Mcal/kg. The weight of the carcass, skin, viscera, fat and uterus were affected by nutritional restriction (P<0,05). There was an increase in the absolute weight of each compartment as there was increase in slaughter weight of animals. The nutritional restriction affected negatively the chemical composition, in grams and in % of EBW, of water and fat in the mammary gland, of water of the viscera and carcass. The chemical composition of water and protein, in grams, and water in g/kg EBW in the skin was affected by the nutritional restriction. Higher proportions of water, protein, fat and energy were observed in the head and feet of the animals in nutritional restriction. The slaughter weights have altered the chemical composition of the body components (P<0,05). With the increase in weight of the animals, there was an increase in the deposition of nutrients in the body. The concentration in g/kg of EBW followed the dynamics of growth of the animal. The concentration of fat and energy increased with increasing weight of slaughter animals while the concentration of water, protein and minerals decreased. The body fat deposition increased with increasing weight and ranged from 295,79 to 774,20 g/kg EBW. The net energy requirement for maintenance was NEm = 86,79 kcal/EBW0,75/day, representing the net energy requirements for maintenance of growing lambs with 20 kg; NEm = 77,63 kcal/EBW0,75/day representing the net energy requirements for maintenance of growing lambs of 30 kg and NEm = 72,73 kcal/EBW0,75/day, representing the net energy requirements for maintenance of growing lambs with 40 kg. The efficiency of utilization of metabolizable energy for maintenance (km) was equaled the 63%, 63% and 60% for the animals of 20 kg 30 kg and 40 kg, respectively. The efficiency of utilization of metabolizable energy for gain (kg) was 33%, 45 % and 20 % for animals with 20 kg, 30 kg and 40 kg, respectively. The nutritional restriction affected negatively the energetics fraction for the animals (P<0,05). The EB intake were 32,74% lower for the animals in feeding restriction, signaling reduction in the order of 37,40% e 61,13% for EN and BE intakes but also for harnessing energy, represented for the relation EM/EB. There was effect of body weight on energy fractions (P<0,05). The EB intake, in kcal/dia, were higher for the animals with 40 kg compared to the others (P<0,05). The higher losses of urinary energy, in kcal/day, were for animals slaughtered at 40 kg compared to the others (P<0,05). The energy loss in faeces and in the form of methane obtained by respirometry, in kcal/UTM, were higher for animals slaughtered at 20 kg compared to the other weights.. The net energy to maintenance were 111,79; 104,35 and 77,78 kcal/BW0,75/day to animals with 20 kg, 30 kg and 40 kg, respectively. The nutritional requirements of female Santa Ines decrease with increasing body weight. The energy requirements for weight gain increase with the increase in empty body weight. Body composition and composition of gain in fat and energy increase with the increase of empty body weight of the animals. The components of the gastrointestinal tract and internal organs with higher metabolic activity were affected by nutritional restriction. Animals in early stages of growth have greater ratio of organs in relation to the weight of empty body indicating earliness of the organs of the gastrointestinal tract. The nutritional restriction altered the chemical composition of water and fat in the mammary gland. The amount of water in the skin, the carcass and viscera were influenced by nutritional restriction. The physiological state of the animal affects the dynamics of nutrient deposition in body components. The Santa Inês lambs submitted the nutritional restriction during growth reduces the intake of dietary energy fractions. The slaughter weights affect energy intake by growing Santa Ines lambs. The Santa Inês animals with 20 kg prioritize the energy intake per unit of metabolic size as necessary to meet their nutritional demands. The gas production by Santa Ines lambs varies with the nutritional plan and slaughter weights.